2023
DOI: 10.1111/1442-1984.12408
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of clonal reproduction in bulbous perennial herb Barnardia japonica sterilized by flower‐smut fungi

Abstract: Flower‐smut fungal infection has been widely observed in many plant species. As plants infected with flower‐smut fungi exhibit visible changes in floral morphology and flower sterility, researchers have intensively studied the effects of the disease on sexual reproduction in host plants. Although most host plants are clonal perennials, the effects of flower‐smut disease on clonal reproduction remain unclear. Here, we investigated the detrimental effects of flower‐smut disease on clonal reproduction of a perenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Unlike clonal reproduction, sexual reproduction provides genetic variation for potential adaptation to long-term environmental changes and promotes long-distance dispersal and colonization of empty habitats (Nathan & Muller-Landau, 2000). Many studies have shown that resource allocation to clonal and sexual reproduction could vary with many ecological factors to maximize fitness for clonal plants (Coelho et al, 2008;Kagaya et al, 2023;Pluess & Stöcklin, 2005;Yang & Kim, 2016;Zhang & Zhang, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike clonal reproduction, sexual reproduction provides genetic variation for potential adaptation to long-term environmental changes and promotes long-distance dispersal and colonization of empty habitats (Nathan & Muller-Landau, 2000). Many studies have shown that resource allocation to clonal and sexual reproduction could vary with many ecological factors to maximize fitness for clonal plants (Coelho et al, 2008;Kagaya et al, 2023;Pluess & Stöcklin, 2005;Yang & Kim, 2016;Zhang & Zhang, 2007).…”
Section: Introductionmentioning
confidence: 99%